Diversity of Orchidaceae from Murum Dam, Belaga, Sarawak, Borneo - Ling Chea Yiing; Julia Sang (Sibbaldia, 2018)
Murum Dam in Sarawak is located about 70 km upstream of Bakun Dam, on the rivers Murum, Danum and Plieran, forming a reservoir over an area of 245 km2. The area consists of mainly lowland to hilly mixed dipterocarp forests, with riparian and alluvial forests along the main rivers and streams, as well as patches of mossy and heath forests. Most of these forests are logged over and some areas have been converted into oil palm plantations. A flora rescue project was carried out to collect selected plant species including orchids from the areas affected by the dam. Most epiphytic orchids were collected from partially submerged trees. Over 2,000 specimens of orchids from 80 genera and c. 276 species were collected from May 2013 to December 2014. The most abundant genus recorded is Bulbophyllum Thouars (c. 44 species). Of these, 37 species are endemic to Borneo, two (Bulbophyllum upupops J.J.Verm., P.O’Byrne & A.L.Lamb and Thrixspermum lingiae P.O’Byrne & Gokusing) are newly described and ten species are new records for Sarawak. The collection of species from this work has provided valuable material for the research and conservation of orchids from vulnerable areas around dams.